Morphological Traits of Maluku Native Forest Clove (Syzygium aromaticum L. Merr & Perry) - Mahulette, Asri Subkhan; Hariyadi, Hariyadi; Yahya, Sudirman; Wachjar, Ade; Alfian, Anggra (Journal of Tropical Crop Science, 2019)
A study was conducted to study the morphology of the forest cloves groups based on their sizes of their leaves, flowers, fruits and seeds, and to determine their potential yield and optimize their production system. The research was conducted for six months from January until June 2018 in Ambon, Maluku Province, Indonesia. The research used a random sampling technique to > 15-year-old trees in productive clove forest maintained by the local farmer in Ambon. The observation and recording was conducted at several stages of clover growth, namely bud sprouting, flower bud, blooming, perianths and anthers senescence, unripe green and ripe fruits. Different size groups of forest cloves have significant differences in the duration of flower and fruit formation. Forest cloves with large leaves, flowers, fruits and seeds had quicker ripening process than the othersize groups, but their fruits were longer to ripen. Flower from the medium size group had the shortest duration to develop its flower and form its fruit, whereas the smallest type took the longest time in fruit formation process but the duration of fruit ripening was similar to those from large morphology. Among the three different sizes of forest cloves in Maluku, the trees with large leaves, flowers, fruits and seeds group are the best to be commercially developed due to its earliest time to harvest and large flower sizes. Forest cloves are best harvested when the flowers are fully matured, indicated by one or two flower buds from one inflorescence have bloomed.